Market Reaction to the Announcement of the Enactment of the Presidential Regulation on the Investment Business Sector - Pratiwi, Kadek Rosita Dewi Indra; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 35 No 3 (2025)DO - 10.24843/EJA.2025.v35.i03.p19, 2025)
The purpose of the study was to examine the market reaction to the announcement of the enactment of Presidential Regulation No. 10 Year 2021. This research uses an event study approach. The population in this study are all companies that are included in the Kompas 100 index on the IDX for the 2020-2021 period and the research sample was taken using the purposive sampling method which resulted in 81 companies. The analytical technique used in this study is the one sample t-test, paired sample t-test, and Wilxocon signed test. The results of the analysis show that there is a market reaction to the announcement of the enactment of Presidential Regulation No. 10 of 2021 concerning the investment business sector as seen from the significant cumulative abnormal return (CAR) on the days around the announcement, and the difference in cumulative abnormal return (CAR) before and after the announcement. Keywords: Market Reaction; Event Study; Presidential Regulation No. 10 Of 2021; Abnormal Returns; Trading Volume Activity.